Peran Patroli Roda Empat Sabhara Dalam Menangani Tawuran Antar Pelajar Di Wilayah Hukum Polresta Bogor Kota - Samosir, Celvin (Police Studies Review, 2020)
The background of this research problem is student brawls that often occur in the Bogor City area. This study discusses the description of the implementation of the patrol unit sabhara Bogor City Police in an effort to deal with student brawls in the Bogor City Polresta, the factors that influence the implementation of sabhara patrol and the role of the unit in dealing with student brawls in the Bogor City Police jurisdiction. This study uses a qualitative approach with field research methods as well as data collection techniques with interviews, observations, and document studies. The location of the study was conducted in the Bogor City Polresta area. The theory used in this research is POAC management theory, role theory, and crime prevention theory, while the concepts used are management elements, patrol concepts, student brawl concepts, and Polri tasks. The results of the study show brawls between students in the Bogor City legal area are quite high in number and the resolution of cases is still lacking. This is due to the lack of optimal four-wheeled patrol in terms of personnel and planning patrol activities. The Bogor Kota Police conducted prevention efforts through the Sabhara Patrol. Based on research conducted, the problem of four-wheeled patrol is human resources, both from the police and from the community. The obstacles faced in implementing the four-wheeled patrol are internal and external constraints. Internal constraints, there are still some members who have not yet carried out vocational education and lack of equipment in conducting patrols and external obstacles, namely that people are still not participating in patrol implementation. Suggestions that can be given (1) can be carried out vocational education for members who have not had the opportunity to follow Dikjur, (2) reduce the maximum unused budget and allocate to the maintenance and maintenance of four-wheeled vehicles and SOP implementation of patrol implementation needs to be revised, (3) do disguising and cooperating with Intel units, (4) increasing the number of four-wheeled patrol personnel as well as adding facilities and infrastructure, (5) there is collaboration between Polri agencies, the government, and the community to reduce the number of brawls between students.